The RUNX Family, a Novel Multifaceted Guardian of the Genome - Bibek Dutta; Motomi Osato (Cells, 2023)
The DNA repair machinery exists to protect cells from daily genetic insults by orchestrating multiple intrinsic and extrinsic factors. One such factor recently identified is the Runt-related transcription factor (RUNX) family, a group of proteins that act as a master transcriptional regulator for multiple biological functions such as embryonic development, stem cell behaviors, and oncogenesis. A significant number of studies in the past decades have delineated the involvement of RUNX proteins in DNA repair. Alterations in RUNX genes cause organ failure and predisposition to cancers, as seen in patients carrying mutations in the other well-established DNA repair genes. Herein, we review the currently existing findings and provide new insights into transcriptional and non-transcriptional multifaceted regulation of DNA repair by RUNX family proteins.